2016
DOI: 10.1155/2016/9239530
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Is an Effective Antihyperglycaemic Agent in a Mouse Model of Wolfram Syndrome 1

Abstract: Wolfram syndrome 1 is a very rare monogenic disease resulting in a complex of disorders including diabetes mellitus. Up to now, insulin has been used to treat these patients. Some of the monogenic forms of diabetes respond preferentially to sulphonylurea preparations. The aim of the current study was to elucidate whether exenatide, a GLP-1 receptor agonist, and glipizide, a sulphonylurea, are effective in a mouse model of Wolfram syndrome 1. Wolframin-deficient mice were used to test the effect of insulin secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…Increased proinsulin:insulin ratio has been shown in mice lacking functional Wfs1 18 . Improper proinsulin processing may also explain the lack of blood glucose lowering effect of depolarizing medication in Wfs1 deficient mice 8 . As both insulin and C-peptide ELISAs used in current study may also cross-react with proinsulin (according to our inquiry to the manufacturer), the improved glycemic control may also in part result from properly processed insulin after liraglutide treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased proinsulin:insulin ratio has been shown in mice lacking functional Wfs1 18 . Improper proinsulin processing may also explain the lack of blood glucose lowering effect of depolarizing medication in Wfs1 deficient mice 8 . As both insulin and C-peptide ELISAs used in current study may also cross-react with proinsulin (according to our inquiry to the manufacturer), the improved glycemic control may also in part result from properly processed insulin after liraglutide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An incretin peptide, GLP-1 regulates glucose homeostasis, metabolism, and neural survival directly on tissues expressing GLP-1 receptors and indirectly through neuronal and endocrine pathways 6 , 7 . Acute treatment with the GLP-1 agonist exenatide has shown a promising anti-diabetic effect in Wfs1 knock-out mice 8 . The GLP-1 agonist Exendin-4 was shown to reduce endoplasmic reticulum (ER) stress in cardiac myocytes and prevent a decrease in activity of sarco/endoplasmic reticulum Ca-ATPase-2a (SERCA2a) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In vivo , exenatide attenuates ER stress and β cell apoptosis in Akita mice and improves glucose levels [181] . A recent study showed that exenatide administration reduces glycemia in exon 8 deleted wfs1 −/− mice [182] . While β cell ER stress was not examined in this study, the data suggest that GLP-1 analogs hold promise for the treatment of Wolfram syndrome diabetes.…”
Section: Therapeutic Modulation Of β Cell Er Stress and Er Stress Sigmentioning
confidence: 99%
“…In 2006, Yusta et al showed that a glucagon-like peptide-1 receptor (GLP-1R) agonist interfered with the ER unfolded protein response, resulting in decreased apoptotic signalling and increased cell survival ( Figure 1 ) [ 44 , 45 ]. In a mouse model of classical WS, the GLP-1R agonist exenatide effectively treated hyperglycaemia [ 35 ]. Treatment of a patient with WS (type 2) with exenatide was associated with a 70% reduction in daily insulin dose, improved glycaemic control, and a 7-fold increase in maximal insulin secretion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that increased cytoplasmic calcium levels activate the calcium-dependent protease, calpain-2, which promotes cellular apoptosis [ 16 , 34 ]. Potential therapeutic targets include molecules which inhibit calcium efflux from the ER, such as dantrolene, via inhibition of the RyR [ 35 ], and rapamycin and pioglitazone, via inhibition of IP3R [ 34 ]. In neuronal WS models, cytosolic calcium appears to be increased under resting conditions and reduced under stimulated conditions [ 28 ].…”
Section: Figurementioning
confidence: 99%